Learning from Nature: Fighting Pathogenic Escherichia coli Bacteria Using Nanoplasmonic Metasurfaces - Alexa Smith; Mahyar Mazloumi; Lucas Karperien; Carlos Escobedo; Ribal Georges Sabat (Advanced Materials Interfaces, 2023)
Abstract Bioinspired nanoplasmonic 3D crossed surface relief gratings and metasurfaces are fabricated on azobenzene molecular glass thin films to create effective antibacterial surfaces. A synergetic mechanical and photothermal interaction at the interface between the nanostructures and the Escherichia coli (E. coli) bacteria results in a significant decrease in the viable bacterial population. In particular, combined exposure to the interfacial nanospikes as well as the evanescent blue and red electromagnetic fields induced by the nanoplasmonic metasurface, results in a 97% reduction of the viable E. coli in only 25 min, when illuminated with a low‐power white light.